The Role of the Venus Application (Vessel Network System) as a Digital Innovation to Increase the Effectiveness of the Crew Change Process at PT Pertamina International Shipping - Siti Aurum Eka Nursasi; Rizqi Aini Rakhman; Sri Mulyanto Herlambang; Faris Nofandi (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study evaluates the Venus (Vessel Network System) application as an in-house digital crewing system that supports the crew change process at PT Pertamina International Shipping. The study used a quantitative descriptive approach supported by direct operational observation. Respondents consisted of 31 internal users who were directly involved in crew scheduling, document verification, approval, monitoring, and interdepartmental coordination through Venus. Data were collected using a Likert-scale questionnaire that measured the importance and performance of 12 system and service indicators, and the results were analyzed using validity testing, reliability testing, and Importance-Performance Analysis (IPA). The findings show that Venus was perceived positively by internal users, with an average importance score of 4.77 (95%) and an average performance score of 4.73 (94%). The application supports scheduling visualization, crew document monitoring, and approval coordination, thereby helping users reduce manual communication and improve operational visibility. However, IPA mapping indicates that four high-importance indicators still require priority improvement: fulfillment of crew change needs, timeliness, data security, and interdepartmental coordination. These gaps show that the effectiveness of Venus should be interpreted as perceived system effectiveness among internal users, while further improvement is needed in system quality, service quality, access control, deadline tracking, and workflow escalation. The study contributes to the evaluation of maritime human-resource information systems by combining user-perception measurement with field observation of digital crew change operations